Climate Information Services and Risk-Contingent Credit: Examining the CGIAR Initiative on Climate Resilience (ClimBeR) Influence and Intervention Impact - Ogada, Maurice Juma (CGIAR System Organization, 2024)
This report evaluates the influence and impact of the CGIAR Initiative on Climate Resilience (ClimBeR), specifically examining the effectiveness of Climate Information Services (CIS) in Guatemala and Senegal, and the Risk-Contingent Credit (RCC) intervention in Kenya. The study employs a mixed-methods approach to assess ClimBeR's contributions to smallholder resilience and food security. Results reveal that ClimBeR's innovative strategies and partnerships have significantly enhanced the reach and utility of CIS, enabling informed farm-level decisions, cost savings, and increased agricultural productivity. The findings underscore the value of scaling and replicating these interventions to support smallholder resilience and adaptive capacity amid climate challenges. The report emphasizes the critical role of tailored partnerships and localized innovations in achieving sustainable agricultural transformation.